Green synthesis of a palladium–polyaniline nanocomposite for green Suzuki–Miyaura coupling reactions1. Issue 43 (14th May 2015) - Dutt, Sunil; Kumar, Raj; Siril, Prem Felix
<x xml:space="preserve">Abstract</x> One pot synthesis of the pd–polyaniline nanocomposite and its catalytic activity in Suzuki–Miyaura coupling reaction in water.